Application of Box-Behnken design for modeling of lead adsorption onto unmodified and NaCl-modified zeolite NaA obtained from biosilica - Terzioglu, Pinar; Yucel, Sevil; Ozturk, Mehmet (IWA PUBLISHING, 2017)
The main objective of the present study was to optimize lead adsorption onto zeolite NaA. For this purpose, to synthesize zeolite NaA under hydrothermal conditions, local wheat husk was precleaned with chemical treatment using hydrochloric acid solution. The unmodified (ZU) and NaCl-modified (ZN) zeolites were characterized by Brunauer-Emmett-Teller, scanning electron microscopy coupled with energy dispersive spectroscopy and X-ray diffraction. The optimization of adsorption process was examined using Box-Behnken Experimental Design in response surface methodology by Design Expert Version 7.0.0 (Stat-Ease, USA). The effects of initial lead (II) concentration, temperature, and time were selected as independent variables. Lack of fit test indicates that the quadratic regression model was significant with the high coefficients of determination values for both adsorbents. Optimum process conditions for lead (II) adsorption onto ZU and ZN were found to be 64.40 degrees C and 64.80 degrees C, respectively, and 90.80 min, and 350 mg L-1 initial lead(II) concentration for both adsorbents. Under these conditions, maximum adsorption capacities of ZU and ZN for lead (II) were 293.38 mg g(-1) and 321.85 mg g(-1), respectively.
Keywords: adsorption; lead; response surface methodology; wheat husk ash; Zeolite A; AQUEOUS-SOLUTION; ACTIVATED CARBON; WASTE-WATER; HUSK ASH; REMOVAL; OPTIMIZATION; BIOMASS; PB(II); PARAMETERS; Engineering; Environmental Sciences & Ecology; Water Resources